Digital health literacy and use of patient portals among Spanish-preferred patients in the United States: a cross-sectional assessment - Philpot, Lindsey M.; Ramar, Priya; Roellinger, Daniel L.; McIntee, Margaret A.; Ebbert, Jon O. (Frontiers in Public Health, 2024)
ObjectiveIndividuals with Limited English Proficiency (LEP), including Spanish-preferred patients, face healthcare challenges due to language barriers. Despite the potential of digital health technologies to improve access and outcomes, there is a “digital divide” with underutilization among vulnerable populations, including Spanish-speaking LEP individuals, highlighting a need for increased understanding and equitable digital health solutions.Materials and methodsA multi-mode, multi-language cross-sectional survey was built based on the Technology Acceptance Model and deployed from a multi-state healthcare practice. Measures included patient-reported comfort level with reading and speaking English, internet and computer access and satisfaction, ability to perform healthcare-related online tasks, and the eHEALS scale of digital health literacy.ResultsA total of 212 Spanish-preferred patients completed the survey (response rate, 212/2,726 = 7.8%), of which 73.6% indicated lack of comfort in reading or writing in English (LEP n = 156). Spanish-speaking individuals with LEP reported higher rates of needing help when learning how to use new technology or devices, reporting difficulty in the evaluation of health information on the internet and being able to differentiate high-quality information from low-quality online health resources, feeling confident in using health information found online to make health decisions, and having lower access to health-related online services than Spanish-speaking individuals without LEP.DiscussionImproving equitable accessibility to digital tools for individuals with LEP seeking healthcare can help to improve their engagement with their providers and promote self-efficacy in their care. Opportunities exist with emerging technologies to develop language-concordant healthcare resources that will improve outcomes for Spanish-preferred patients.